Fundamentals of artificial intelligence and machine learning - Pradhan, Manaswini (New Delhi D. P. S. Publishing House, 2022)
The advances in Electronic industry, with a substantial reduction in the cost of components and shrinkage in computer dimensions have made computer technology much more affordable for people even in a developing country like India. This book about the science of artificial intelligence.
Keywords: Technology Sector; Artificial Intelligence; Machine Learning